Separable English phrasal verbs: a comparison of L1 English speakers and L1 Spanish speakers of L2 English - Dongilli, Sophia J. (Kansas State University, 2015)
How to teach phrasal verbs to L2 learners of English has been the subject of debate in Teaching English as a Foreign Language (TEFL) courses and materials alike. These multi-part verbs, consisting of a verb and one or more particles, convey a new lexical meaning different from their individual parts. Further complicating this is the fact that some transitive phrasal verbs can be separated from their particles to varying degrees by a direct object. Though variables affecting verb-particle separation lie below the level of consciousness for most native speakers, they make the acquisition of particle placement difficult for L2 English language learners. Additionally, the presentation of these verbs in EFL textbooks and university English language programs (ELPs) is inadequate. TEFL textbooks tend to place emphasis on the lexical acquisition of phrasal verbs, ignoring separable versus non-separable distinctions. However, native English speakers separate phrasal verbs from their particles about 66.5% of the time in spoken conversation. In order to determine whether traditional textbook problems associated with phrasal verb presentation persist, I analyzed eleven TEFL textbooks used in Kansas State University’s ELP. I also administered a grammaticality judgment survey in order to find out whether L1 Spanish speakers of L2 English view separation of transitive phrasal verbs and their particles to be grammatical. L1 Spanish Speakers of L2 English are disadvantaged by the fact that their native language is verb-framed, meaning that it does not make use of particles in the same way that English does. It is for this reason that native Spanish-speakers of L2 English constitute the experimental group in this study. The results of the TEFL textbook analysis reveal that none of the eleven textbooks analyzed could stand alone in the classroom to effectively teach phrasal verbs. The results of the grammaticality judgment survey show that L1 Spanish speakers of L2 English differ at a statistically significant level from L1 American English speakers in their acceptability of phrasal verb-particle separation. These findings have pedagogical implications for TEFL instructors, textbook writers, and English language programs, and demonstrate the need for more extensive and authentic phrasal verb instruction.
Keywords: Separable; Phrasal verbs; English; Spanish; TEFL; Particle placement; English as a Second Language (0441); Foreign Language Instruction (0444)